Phytochemical Analysis, Biological Activity and In Silico Molecular Docking Studies of Constituents of Scadoxus multiflorus (Martyn) Raf. - Ilili Dine (ASTU, 2023)
Natural products generated from medicinal plants are among the most recent approaches in the production of herbal product-based drugs owing to high efficacies and fewer adverse effects. Scadoxus multiflorus (Amaryllidaceae) is a widespread ornamental plant of tropical east and South Africa. It is traditionally used for the treatment of many respiratory problems (bronchitis, asthma, pneumonia, sinusitis, etc., and even tuberculosis), scabies, dropsy, and wound healing. The root of the Scadoxus multiflorus (400 g) was successively extracted with n-hexane, chloroform, and methanol to afford 1.00, 1.13, and 12.25% yields respectively. Silica gel column chromatographic separation of the n-hexane and chloroform extract afford five compounds identified as β-sitosterol (29), 11-hentriacontene (30), 5, 12-henicosadiene (31), lindcarpine derivatives (32), and linolieamide (33). The structures of the isolated compounds were characterized using UV-Vis and NMR spectroscopic techniques (1H NMR, 13C NMR, and DEPT-135). The crude extract and isolated compounds were evaluated in vitro for their antibacterial activities using the disc diffusion method against six bacterial strains. Promising inhibition zone values were observed by β-sitosterol (29) (15±0.00mm) and 5, 12-henicosadiene (31) (15±0.00mm) against S. typhimurium compared to ciprofloxacin (31.3±1.97). Linoliamide (33) and β-sitosterol (29) had slightly highest scavenging of DPPH free radicals than other isolated compounds but lower scavenging when compared to ascorbic acid. In silico molecular docking analysis revealed that β-sitosterol (29) exhibited better docking efficiency (E.coli) enzyme DNA gyrase (-9.1 kcal/mol) and human topoisomerase II β (-9.6 kcal/mol) when compared to Amoxicillin (− 7.6 kcal/mol) and Abiraterone (-11.8 kcal/mol) respectively. This suggests that compounds 29 may be used as potential drug lead candidates.
Keywords: S. multiflorus, phytochemical screening, biological activity